The Impact of Singapore’s Language Policies on Singaporean Chinese Youth’s Language Attitudes Toward Mandarin Chinese - Gisselberg, Jessika (My University, 2024)
In this bachelor's thesis, I examine the effects of Singapore's language policies on the language attitudes of Singaporean Chinese youth toward Mandarin Chinese. I discuss the literature on the ideological backgrounds of Singapore's language policies and how they are reflected in the attitudes of Singaporean Chinese. Additionally, I discuss attitudes towards Mandarin Chinese and consider the importance of other variations of the Chinese language spoken in Singapore in the formation of language attitudes. Research on language attitudes towards Mandarin Chinese in Singapore is still scarce, so this thesis brings together existing literature on the topic and brings a new perspective to the connection between language policy and language attitudes. The studied literature emphasizes the pragmatic nature of Singapore's language policy, according to which languages ​​are prioritized based on their practical benefits. This pragmatism is also reflected in the language attitudes of the Singaporean Chinese, as according to the results of the surveys, the Singaporean Chinese find Mandarin Chinese useful and necessary and prefer it compared to other Chinese variations spoken in Singapore. However, the studies also show that the participants generally do not attach a great cultural value to Mandarin Chinese, but value it precisely because of the economic opportunities associated with it. They reflect on the importance of variations of English and other Chinese languages ​​in the formation of language attitudes and their importance in the development of the identity of the Singaporean Chinese community. In the future, more extensive research on language attitudes towards Mandarin Chinese is needed, and sample sizes in participants should be diversified in order to achieve more reliable results. In addition, research could be deepened into the variations of Chinese spoken in Singapore and their relationship with Mandarin Chinese.

Tässä kandidaatintutkielmassa tarkastelen Singaporen kielipolitiikan vaikutuksia singaporenkiinalaisten mandariinikiinaan kohdistuviin kieliasenteisiin. Käsittelen kirjallisuutta Singaporen kielipolitiikan ideologisista taustoista ja siitä, miten ne heijastuvat singaporenkiinalaisten asenteisiin. Tämän lisäksi käsittelen mandariinikiinaan kohdistuvia asenteita ja pohdin muiden Singaporessa puhuttavien kiinan kielen variaatioiden merkitystä kieliasenteiden muodostumisessa. Tutkimus mandariinikiinaan kohdistuvista kieliasenteista Singaporessa on vielä vähäistä, joten tämä tutkielma kokoaa yhteen olemassa olevaa tutkimusta aiheesta ja tuo uuden näkökulman kielipoliitikan ja kieliasenteiden yhteyteen. Tutkittu kirjallisuus painottaa Singaporen kielipolitiikan pragmaattisuutta, jonka mukaisesti kieliä priorisoidaan niiden käytännöllisten hyötyjen perusteella. Tämä pragmaattisuus näkyy myös singaporenkiinalaisten kieliasenteissa, sillä tutkimuksien tulosten mukaan singaporenkiinalaiset kokevat mandariinikiinan hyödylliseksi ja tarpeelliseksi ja suosivat sitä suhteessa muihin Singaporessa puhuttaviin kiinan variaatioihin. Tutkimukset osoittavat kuitenkin, että osallistujat eivät yleisesti liitä mandariinikiinaan suurta kulttuurista arvoa vaan arvostavat sitä nimenomaan siihen miellettyjen ekonomisten mahdollisuuksien vuoksi. Niissä pohditaan englannin ja muiden kiinan kielten variaatioiden merkitystä kieliasenteiden muotoutumisessa ja niiden merkitystä singaporenkiinalaisen yhteisön identiteetin kehittymisessä. Jatkossa tarvitaan laajempaa tutkimusta mandariinikiinaan kohdistuvista kieliasenteista, ja tutkittavien otantaa tulisi monipuolistaa saadakseen luotettavampien tuloksien saavuttamiseksi. Lisäksi tutkimusta voisi syventää Singaporessa puhuttaviin kiinan variaatioihin ja niiden suhteesta mandariinikiinaan.
Keywords: language attitudes, language policies, Singapore, Chinese linguistics